Analysis Determinant Factors of Innovation Speed in SMEs Manufacturing - Tarmidi, Didi; Munawar, Fansuri; R, Susanto Hendiarto; Mega Utama, Zahera; Utami Saptaningrum, Dewi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the role of innovation collaboration, management support, and knowledge sharing as factors suspected to increase innovation speed in SMEs manufacturing. This study took a sample of SMEs manufacturing, which consisted of five main industrial categories, namely textile industry, handicraft industry, shoe & bag industry, food & beverage industry, and various industries. Sampling was carried out on 100 owners or managers of SME manufacturing in Bandung and surrounding areas because the area is one of the centers of SME manufacturing in West Java. Data analysis in this study used a structural equation model based on partial least squares (SEM-PLS). The results of testing of the research hypothesis show that the variables of innovation collaboration and management support have a positive and significant effect on innovation speed, but the variable of knowledge sharing does not have a positive and significant impact on innovation speed. Research implications to the owner or manager to utilize innovation collaboration with external partners, especially the collaboration with consumers. In addition, it is expected that the owner or manager can create a work atmosphere that supports innovation.